2020
DOI: 10.1186/s12938-019-0744-0
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of a multimodal MRI-based radiomics signature for the preoperative prediction of the histological subtype in patients with non-small-cell lung cancer

Abstract: Background: Non-invasive discrimination between lung squamous cell carcinoma (LUSC) and lung adenocarcinoma (LUAD) subtypes of non-small-cell lung cancer (NSCLC) could be very beneficial to the patients unfit for the invasive diagnostic procedures. The aim of this study was to investigate the feasibility of utilizing the multimodal magnetic resonance imaging (MRI) radiomics and clinical features in classifying NSCLC. This retrospective study involved 148 eligible patients with postoperative pathologically conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…Many studies have shown that radiomics features have great potential to be the maker for tumor phenotype (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and found Adc can be differentiated from Sqc by radiomics (17)(18)(19)(20)(21)(22)(23). However, The data sets of those studies only included Adc and Sqc, that is to say, the accuracy of those models will be affected by other histological subtypes of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that radiomics features have great potential to be the maker for tumor phenotype (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and found Adc can be differentiated from Sqc by radiomics (17)(18)(19)(20)(21)(22)(23). However, The data sets of those studies only included Adc and Sqc, that is to say, the accuracy of those models will be affected by other histological subtypes of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…After the feature extraction from each voxel, a total of 1159 features were generated for each voxel to characterize its properties and group. Considering that not all the features contributed greatly to classify the group of each voxel, and feature redundancy might actually exist and impair the capability of the classification model, feature selection was performed using support vector machine (SVM)-recursive feature elimination (RFE) approach [24][25][26]. The results were shown in Fig.…”
Section: Demographics Of the Subjectsmentioning
confidence: 99%
“…After the feature extraction from each voxel, a total of 1159 features were generated for each voxel to characterize its properties and group. Considering that not all the features contributed greatly to classify the group of each voxel, and feature redundancy might actually exist and impair the capability of the classi cation model, feature selection was performed using support vector machine (SVM)-recursive feature elimination (RFE) approach [24][25][26]. The results were shown in Fig.…”
Section: Demographics Of the Subjectsmentioning
confidence: 99%